2021
DOI: 10.1136/bjsports-2020-103475
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health are associated with physical therapy use: a systematic review

Abstract: ObjectiveThe purpose of this systematic review is to identify and summarise the social determinants of health (SDH) cited in the literature and evaluate their association with individuals using physical therapy services.DesignA systematic review using qualitatively synthesised information to describe the association between SDH and physical therapy use.Data sourcesThe electronic databases Medline, Embase and Scopus were searched from inception to February 2021, identifying observational and qualitative studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Future studies exploring other variations in care between patients with ALL treated by a hematology/oncology attending versus other physicians may help improve the quality of care for children with ALL. 36 We also found that PT utilization had minimal variation by geographic region. In unadjusted analyses, we found that patients who received PT were more likely to be treated in hospitals in the West than those who did not receive PT, similar to a national study of PT utilization among adult patients with vestibular disorders that found PT was more frequently provided to patients in the West.…”
Section: Factors Associated With Pt Servicesupporting
confidence: 51%
“…Future studies exploring other variations in care between patients with ALL treated by a hematology/oncology attending versus other physicians may help improve the quality of care for children with ALL. 36 We also found that PT utilization had minimal variation by geographic region. In unadjusted analyses, we found that patients who received PT were more likely to be treated in hospitals in the West than those who did not receive PT, similar to a national study of PT utilization among adult patients with vestibular disorders that found PT was more frequently provided to patients in the West.…”
Section: Factors Associated With Pt Servicesupporting
confidence: 51%
“…The highest proportion of visits were covered under private insurance, in concordance with data illustrating a higher likelihood of PT use for private insurance holders. 3 Interestingly, a subanalysis of telehealth utilization before and after official reopening of the PT center revealed similar differences in patient characteristics with those identified between in-person and telehealth visits. That is, after September 2020 (reopening date) compared with before, telehealth users were more often female, lived farther away and in nonurban postal codes, had lower income, and more frequently carried Medicaid or Medicare health insurance.…”
Section: Discussionmentioning
confidence: 68%
“…The highest proportion of visits were covered under private insurance, in concordance with data illustrating a higher likelihood of PT use for private insurance holders. 3 …”
Section: Discussionmentioning
confidence: 99%
“…Over the past 5 years, a growing emphasis has been placed on the biopsychosocial model of health care, aiming to assess the psychosocial aspects of health alongside the more well-accepted biological factors associated with disease, injury, or pathology, to develop a plan of care that considers the whole person. A recent systematic review highlighted predisposing factors as they relate to social determinants of health that impact the use of physical therapy services (8). This research can cautiously be extrapolated to other areas of wellness, prevention, and exercise rehabilitation, suggesting that health care professionals should consider marketing and engagement strategies that promote exercise and resistance training to individuals in rural areas, with lower levels of education, or in a lower socioeconomic class, as these are more likely to be a barrier to care.…”
Section: Barriers To Implementing Comprehensive Resistance Training P...mentioning
confidence: 99%